Metabolic Engineering of Oleaginous Yeast Yarrowia lipolytica for Overproduction of Fatty Acids - Ghogare, Rishikesh; Chen, Shulin; Xiong, Xiaochao (Frontiers in Microbiology, 2020)
The oleaginous yeast Yarrowia lipolytica has attracted much attention due to its ability to utilize a wide range of substrates to accumulate high lipid content and its flexibility for genetic manipulation. In this study, intracellular lipid metabolism in Y. lipolytica was tailored to produce fatty acid, a renewable oleochemical and precursor for production of advanced biofuels. Two main strategies, including blocking activation and peroxisomal uptake of fatty acids and elimination of biosynthesis of lipids, were employed to reduce fatty acids consumption by the native pathways in Y. lipolytica. Both genetic modifications improved fatty acids production. However, disruption of the genes responsible for assembly of nonpolar lipid molecules including triacylglycerols (TAGs) and steryl esters resulted in the deleterious effects on the cell growth. The gene tesA encoding thioesterase from Escherichia coli was expressed in the strain with disrupted faa genes encoding fatty acyl-CoA synthetases and pxa1 encoding peroxisomal acyl-CoA transporter, and the titer of fatty acids resulted in 2.3 g/L in shake flask culture, representing 11-fold improvement compared with the parent strain. Expressing the native genes encoding acetyl-CoA carboxylase and hexokinase also increased fatty acids production, although the improvement was not as significant as that with tesA expression. Saturated fatty acids including palmitic acid (C16:0) and stearic acid (C18:0) increased remarkably in the fatty acid composition of the recombinant bearing tesA compared with the parent strain. The recombinant expressing tesA gene resulted in high lipid content, indicating the great fatty acids producing potential of Y. lipolytica. The results highlight the achievement of fatty acids overproduction without adverse effect on growth of the strain. Results of this study provided insight into the relationship between fatty acid and lipid metabolism in Y. lipolytica, confirming the avenue to reprogram lipid metabolism of this host for overproduction of renewable fatty acids.